Hubungan Harga Diri Dengan Rasa Aman Pada Wanita Yang Mengalami Catcalling - Siburian, Cindy Putri Anggriani; Simbolon, Hotpascaman (Jurnal Teologi Cultivation, 2025)
This study examines the relationship between self-esteem and the sense of safety among women who have experienced catcalling, a form of verbal harassment in public spaces that is often underestimated yet has profound psychological effects. Using a correlational quantitative approach, the study involved early adult female respondents aged 18–24 who had encountered catcalling. The instruments used were self-esteem and safety perception scales, developed based on valid psychological indicators. The findings indicate a significant positive correlation between self-esteem and the sense of safety. Women with higher self-esteem tend to show greater emotional resilience and feel more secure in facing verbal harassment. Conversely, low self-esteem is associated with increased anxiety, helplessness, and perceived threats in social spaces. These results underscore the importance of a humanistic perspective in fostering social awareness, empowering women, and safeguarding psychological integrity in a culture that remains permissive toward symbolic violence.